1989
DOI: 10.1099/0022-1317-70-6-1347
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Causes Amplification of Recombinant Plasmids Containing Simian Virus 40 Sequences

Abstract: SUMMARYSimian virus 40 (SV40) DNA, inserted into a plasmid vector, does not replicate when transfected into baby hamster kidney cells. However, when the recipient cells are superinfected with herpes simplex virus type 1 (HSV-1), extensive amplification of the introduced plasmid occurs. Deletion of the late SV40 region or part of the coding sequences of the small tumour (t) antigen has no effect on the efficiency of amplification, whereas manipulations affecting either the SV40 origin of replication or the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…It has been shown that SV40 origin-containing plasmids replicate in hamster cells upon infection with HSV (Matz, 1989). This heterologous SV40 DNA synthesis is mediated by the HSV replication genes (UL5, UL8, UL29, UL30, UL42 and UL52; Heilbronn & zur Hausen, 1989) but does not require the UL9 gene (Heilbronn & zur Hausen, 1989;Matz, 1989). It seems that T antigen substitutes for UL9 protein on SV40 DNA and makes the SV40 DNA accessible to the other HSV-specific DNA replication proteins.…”
Section: Orf (Mcgeochmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that SV40 origin-containing plasmids replicate in hamster cells upon infection with HSV (Matz, 1989). This heterologous SV40 DNA synthesis is mediated by the HSV replication genes (UL5, UL8, UL29, UL30, UL42 and UL52; Heilbronn & zur Hausen, 1989) but does not require the UL9 gene (Heilbronn & zur Hausen, 1989;Matz, 1989). It seems that T antigen substitutes for UL9 protein on SV40 DNA and makes the SV40 DNA accessible to the other HSV-specific DNA replication proteins.…”
Section: Orf (Mcgeochmentioning
confidence: 99%
“…Transfection and analysis of plasmid replication were carried out as previously described (Matz, 1989). It has been shown that SV40 origin-containing plasmids replicate in hamster cells upon infection with HSV (Matz, 1989). This heterologous SV40 DNA synthesis is mediated by the HSV replication genes (UL5, UL8, UL29, UL30, UL42 and UL52; Heilbronn & zur Hausen, 1989) but does not require the UL9 gene (Heilbronn & zur Hausen, 1989;Matz, 1989).…”
Section: Orf (Mcgeochmentioning
confidence: 99%
See 3 more Smart Citations